1994
DOI: 10.1021/jm00032a019
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[f]quinazoline Inhibitors of Thymidylate Synthase: Methyleneamino-Linked Aroylglutamate Derivatives

Abstract: Syntheses of several new inhibitors of thymidylate synthase (TS) structurally related to folic acid are described in which the pterin portion of the folate molecule is replaced by a benzo[f]quinazoline moiety, but which retain the natural methyleneamino link to the benzoylglutamate side chain. The effect on enzyme activity and cytotoxicity of various changes in the structure of the (p-aminobenzoyl)glutamate side chain are reported. Replacement of the benzamide portion of the (p-aminobenzoyl)glutamate moiety wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…aFrom Dev et al [46].bFrom Dolnick and Cheng [25].cFrom Davisson et al [26].dFrom Pendergast et al [44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…aFrom Dev et al [46].bFrom Dolnick and Cheng [25].cFrom Davisson et al [26].dFrom Pendergast et al [44].…”
Section: Resultsmentioning
confidence: 99%
“…mTHF solutions were stored under argon at −20°C. 1843U89 was synthesized as previously reported [44].…”
Section: Methodsmentioning
confidence: 99%
“…TS methylates the 5-carbon of 5’-deoxyuridine monophosphate (dUMP) to form thymidine monophosphate (TMP) using 5,10-methylene THF as a cofactor. TS is the target for many anticancer agents including pemetrexed, ZD1694, 1843U89, AG331, and AG337 [11, 1318]. …”
Section: Introductionmentioning
confidence: 99%
“…effects. 3339 For example, Pendergast et al 40 observed that a 2′-fluoro substitution of a benzo[ f ]quinazoline antifolate increased antitumor activity, which was attributed to the conformational restriction of the side-chain L-glutamate via a fluorine−hydrogen bond. 41 …”
Section: Introductionmentioning
confidence: 99%